Aplikasi Perhitungan Pajak Karyawan Pada PTPN VII Unit Tulung Buyut - Fatmawati Isnaini; Maria Nainggolan (Journal of Engineering and Information Technology for Community Service, 2022)
PTPN VII Unit Tulung Buyut is one of the businesses engaged in rubber plantations. Income tax data processing is currently using Microsoft Excel and making reports is still simple by utilizing the forms that have been made previously. so that existing problems will result in inaccurate income tax data reports so that it can result in disputes for each income tax data report. The purpose of making this application is to obtain a more advanced application program by utilizing programming languages in its development. Data collection methods used are interviews, observations, documentation and literature review. The approach used is object-oriented and uses the Extreme Programming method as a system development process. System development tools are in the form of Document Flowcharts (BAD), and Unified Modeling Language (UML), namely use case diagrams, class diagrams, activity diagrams and sequence diagrams that can help to design a pPph 21 taxation system. The software on this system uses the Java programming language to speed up the process of paying employee income taxes and the MySQL database is used to store employee report data and income tax payments